2021
DOI: 10.1002/cncr.33995
|View full text |Cite
|
Sign up to set email alerts
|

Transoral robotic surgery adoption and safety in treatment of oropharyngeal cancers

Abstract: Background Transoral robotic surgery (TORS) was approved by the Food and Drug Administration in 2009 for the treatment of oropharyngeal cancers (oropharyngeal squamous cell carcinoma [OPSCC]). This study investigated the adoption and safety of TORS. Methods All patients who underwent TORS for OPSCC in the National Cancer Data Base from 2010 to 2016 were selected. Trends in the positive margin rate (PMR), 30‐day unplanned readmission, and early postoperative mortality were evaluated. Outcomes after TORS, nonrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
1
20
0
1
Order By: Relevance
“…Studies comparing mortality in the non-surgical group for chemoradiation or radiation only groups will help determine if surgical complications or non-surgical issues contributed to mortality. Although the exact cause underlying this association is unknown, one recently published study found a similar association due to younger patients presenting with more advanced nodal disease ( 30 ). In agreement with this study, we found that younger patients (<65 years) were observed to have higher N-category (N2/3) disease (<65 years: 1920/2563 vs ≥65 years: 643/2563; p<0.01) and therefore this association may be a reflection of the previously addressed impact of age on perioperative mortality.…”
Section: Discussionmentioning
confidence: 93%
“…Studies comparing mortality in the non-surgical group for chemoradiation or radiation only groups will help determine if surgical complications or non-surgical issues contributed to mortality. Although the exact cause underlying this association is unknown, one recently published study found a similar association due to younger patients presenting with more advanced nodal disease ( 30 ). In agreement with this study, we found that younger patients (<65 years) were observed to have higher N-category (N2/3) disease (<65 years: 1920/2563 vs ≥65 years: 643/2563; p<0.01) and therefore this association may be a reflection of the previously addressed impact of age on perioperative mortality.…”
Section: Discussionmentioning
confidence: 93%
“…When considering outcomes after TORS, another NCDB study by Hanna et al found the rate of BOT OPSCC positive margins was higher than tonsillar OPSCC, but this was nonsignificant [ 55 ]. Interestingly, Hanna et al and another more recent NCDB review from Oliver et al found that high volume cancer centers reduced their positive margin rates by almost half compared to low volume centers (12.7% versus 21.9% and 11.2% to 19.3%) [ 55 , 58 ]. Furthermore, Oliver et al found that BOT positive margins were reduced by around 6% when comparing rates from 2011 to 2016 [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Hanna et al and another more recent NCDB review from Oliver et al found that high volume cancer centers reduced their positive margin rates by almost half compared to low volume centers (12.7% versus 21.9% and 11.2% to 19.3%) [ 55 , 58 ]. Furthermore, Oliver et al found that BOT positive margins were reduced by around 6% when comparing rates from 2011 to 2016 [ 58 ]. A systematic review on TORS found that specific procedures were more difficult due to the structural components of the robot, with BOT resections being more likely to undergo conversion to an open approach [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be magnified in transoral robotic surgery (TORS) due to limited haptic feedback and anatomic constraints preventing palpation of the tumour during resection. Positive margin rates have improved with increased experience with TORS, but remain high at nearly 16% nationally 2 and 26% at low‐volume centres 3,4 . The ability to obtain favourable oncologic outcomes with TORS on even locally advanced tumours has been demonstrated, 5,6 but avoidance of postoperative adjuvant therapy is dependent on ability to obtain negative margins amongst other factors 7,8 .…”
Section: Introductionmentioning
confidence: 99%